MEMBANGUN BUDAYA AMAN BENCANA MELALUI INFORMASI DAN EDUKASI PADA REMAJA KARANG TARUNA PERUMAHAN BANGUNTAPAN ASRI - Arimurti, Dyah Arum; Baihaqi, Habibah Khusna (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Indonesia, which is in the subduction zone, is prone to natural disasters such as earthquakes and tsunamis. This community service activity aims to increase the awareness of the youth of the Banguntapan Asri Housing Youth Organization regarding earthquake and tsunami disaster mitigation. Through interactive zoominar, participants were given material on the causes, impacts, and mitigation measures of disasters. The methods used include pre-test, post-test, and discussion sessions. The results of the evaluation showed an increase in participants' knowledge about earthquake and tsunami mitigation. However, there are still several questions that need to be answered further to improve similar programs in the future. Overall, this activity makes a positive contribution to efforts to build a disaster safe culture in the community